A Scientometric Analysis of Hajj Service Literature During Covid-19 - Nadia Nurul Izza (SMART Insight, 2023)
Hajj is the fifth pillar of Islam and is unique worship so that almost all Muslims want to carry out this worship. During the COVID-19 pandemic, a solution is needed to provide the best service to pilgrims. Every year, new services are developed by utilizing advances in technology and the service industry to help prospective pilgrims who plan to perform the pilgrimage. Research related to the theme of Hajj service is constantly increasing every year. This study aims to determine research trends regarding Hajj service published by dimensions-indexed journals. The method used is descriptive statistical analysis with meta-analysis and bibliometry of secondary data in the form of 142 published papers in the last four years which are then processed using Microsoft Excel 2019. The data is then processed and analyzed using the VOSviewer application to find out the bibliometric map of the Hajj service research development. The results of this study are that digitization in hajj services provides convenience for hajj pilgrims and increases efficiency. This study consists of 6 clusters, with the red cluster being the most significant cluster with 16 authors, namely Nouf Hameed, Osama Hamad, Naif Olaythah, Fareed Ali, Mesfer, Ahmad M., Majed Mohammad, Yousef Ahmed, Abdulrahman Safar, Taha Muhammad, Yasir Abdulraheem, Lamees Essa, Hani Mohammad, Nezar Adnan, Nojoud Adnan, and Wael H. This study opens a new research direction that is practical, which was chosen based on a holistic review of the current technological analytic survey, which is essential to be considered for improving Hajj services and Umrah with today's technology. However, it is also necessary to research the development of the literature.